Ngā Kaupapa Wawata me Uara: A narrative review exploring Tiriti o Waitangi-centred population health programmes in Aotearoa New Zealand - Wright, Karen; Dehar, Aria; Sharpe, Sarah; Silailai, Luisa; Fernandes, Basil; Jones, Rhys (The International Indigenous Policy Journal, 2024)
Globally, Indigenous Peoples experience widespread health inequities. Treaties provide a potential framework to uphold Indigenous rights and progress health equity. Te Tiriti o Waitangi (Māori language version of the Treaty of Waitangi) established the relationship between Māori, the Indigenous people of Aotearoa (New Zealand), and the British Crown. Grounded in Kaupapa Māori theory, this literature review used an Indigeneity-Grounded Analysis (IGA) policy lens to identify four characteristics of Tiriti-centred population health programmes: whanaungatanga (relationships), pro-equity actions, Te Ao Māori (Māori worldviews), and accountability. Although the evidence-base is emergent, a rights-based approach identifies the centrality of Indigenous self-determination, structural and system transformation, and freedom from discrimination. Indigenous knowledge provides the foundation for treaty-centered policy supportive of Indigenous rights and health equity.